2022
DOI: 10.3389/fmed.2022.855296
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoint Stimulation Combined With Auricular Acupressure Reduces Postoperative Delirium Among Elderly Patients Following Major Abdominal Surgery: A Randomized Clinical Trial

Abstract: BackgroundPostoperative delirium is common in elderly patients following major surgery. This study aimed to assess the effect of transcutaneous electrical acupoint stimulation combined with auricular acupressure on the incidence of postoperative delirium among older patients undergoing major abdominal surgery.MethodsIn this single-center, randomized controlled clinical trial, 210 patients aged 65 years or older undergoing major abdominal surgery were randomized to receive either intervention treatment (transcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…PSD may worsen neurocognitive dysfunction, impair the psychological state, and delay the recovery after surgery among elderly patients, leading to heavy emotional and financial burdens [ 44 ]. Substantial evidence shows that improving sleep quality could minimize the risk of postoperative delirium and enhance the quality of recovery in elderly patients [ 45 , 46 ]. However, non-pharmacological interventions such as earplugs and eye masks were ineffective to improve sleep quality after major abdominal surgery [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSD may worsen neurocognitive dysfunction, impair the psychological state, and delay the recovery after surgery among elderly patients, leading to heavy emotional and financial burdens [ 44 ]. Substantial evidence shows that improving sleep quality could minimize the risk of postoperative delirium and enhance the quality of recovery in elderly patients [ 45 , 46 ]. However, non-pharmacological interventions such as earplugs and eye masks were ineffective to improve sleep quality after major abdominal surgery [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism is related to improving cerebral blood flow and brain metabolism, lowering the permeability of the blood–brain barrier, and reducing neuroinflammation and nerve cell damage. Because pain and sleep disorders are possible confounders of delirium severity, stimulation of PC6 ( Neiguan ) and LI4 ( Hegu ) might reduce the incidence of POD by attenuating the extent of postoperative pain and improving sleep quality ( Fan et al, 2022 ). Regrettably, the question of which specific acupoints, TEAS frequency, intensity, and intervention time are most beneficial could not been solved because of the different combinations of acupoints, the different stimulation parameters, and the limited number of included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that stimulation of PC6 (Neiguan) and LI4 (Hegu) can be used to assist anesthesia, reduce anesthetic use, repress surgical stress, and improve cognitive function (Wang et al, 2014;Matsumoto-Miyazaki et al, 2017). Its mechanism is related to improving cerebral blood flow and brain metabolism, lowering the permeability of the blood-brain barrier, and (Fan et al, 2022). Regrettably, the question of which specific acupoints, TEAS frequency, intensity, and intervention time are most beneficial could not been solved because of the different combinations of acupoints, the different stimulation parameters, and the limited number of included studies.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A trend of reduced incidence of POD (6.3% vs 25%) was reported when geriatric patients with silent lacunar infarction received TEAS as an intervention before and during spinal surgery. [27] Likewise, an accordant effect of acupuncture was observed by Fan et al [28] at preventing delirium, which showed that the combination of TEAS and auricular acupressure reduced the incidence and severity of POD in elderly patients undergoing major abdominal surgery, as compared with standard care. Li et al [29] found that scalp acupuncture performed during operation could reduce the incidence of POD and shorten the post-operative hospital stay in elderly patients undergoing hip replacement.…”
Section: Beneficial Effects Of Acupuncture On Podmentioning
confidence: 94%